Asporogenic Bacillus megaterium mutant 27-36 degrades intrinsically short-lived proteins but fails to convert most of other proteins to a short-lived fraction - Chaloupka, J; Kucerová, H; Strnadová, M; Votruba, J; Ludvík, J (Biochemistry and molecular biology international, 1996)
Asporogenic mutant blocked in the 0-II sporulation stage degraded pulse-labelled proteins in the sporulation medium at the same rate as the parental strain for the first two hours. The degraded fraction was mostly composed of intrinsically short-lived proteins which were degraded even after enriching the medium with amino acids and growth resumption. Proteins accessible to degradation because of nutritional shift down formed a lesser proportion of this fraction. The acceleration of protein turnover in the parent strain during the irreversible sporulation phase was not developed in the mutant. A first order kinetic model of protein degradation was used for parameter estimation. Ca(2+)-dependent intracellular serine proteinase was synthesized in an inactive form, which was activated by increasing Ca2+ concentration to 30 mM.
Keywords: vápník; bakteriální proteiny; Bacillus megaterium; spory bakteriální; Calcium; kinetika; Mutation; mutace; Spores, Bacterial; Bacterial Proteins; Kinetics; Serine Endopeptidases; serinové endopeptidasy